"Análisis del desgaste prematuro en elementos mecánicos de la caja automática Ecolife usada en buses marca Zhongtong." - Loor Hernández, Evelin Lisseth (2021)
The proposed investigation came from the need to determine the factors that intervene for the premature wear of mechanical elements of an Ecolife automatic transmission, in the buses of a certain fleet; With this investigation, there will be enough tools to determine the correct procedure to be followed by the unit owners, thus avoiding the problem presented. This class of automatic boxes are intended for mass transportation vehicles, the same ones that are beginning their operation in the country, their costs being high due to the technology they present; What we want to achieve with this investigation is to determine a correct and accurate maintenance plan to significantly eliminate premature wear, and confirming that what is indicated by the manufacturer both in the type of lubricating fluid and in the mode of operation, together with others factors is the right thing to do and will prevent financial loss. To obtain the expected results, the research will be limited to vehicles of the same type and that work on the same routes, in order to ensure the viability of this research, obtaining positive and expected results for this fleet.